2001
DOI: 10.1080/08856250110074382
|View full text |Cite
|
Sign up to set email alerts
|

The perceived needs of support of parents and classroom teachers a comparison of needs in two microsystems

Abstract: The aim of this study was to describe and compare from a systems perspective the perceived needs of parents and teachers of school-age children with intellectual impairments. The relationship between type and degree of impairment to perceived needs was analysed. Comparisons revealed that while the parents and teachers differed regarding their respective needs, they agreed on speci c informational needs. It was found that certain child characteristics in interaction with contextual factors evoked speci c needs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 18 publications
3
12
0
3
Order By: Relevance
“…Although previous studies have identified characteristics that are associated with parents' perceived unmet needs (Ellis et al 2002;Granlund and Roll-Pettersson 2001;Kogan et al 2008;Siklos and Kerns 2006), to our knowledge, this is the first to examine these factors systematically in a conceptual framework. Planning for comprehensive services is held back by our limited understanding of the characteristics associated with greater unmet need among families of children with ASD.…”
Section: Methodological Strengthsmentioning
confidence: 93%
“…Although previous studies have identified characteristics that are associated with parents' perceived unmet needs (Ellis et al 2002;Granlund and Roll-Pettersson 2001;Kogan et al 2008;Siklos and Kerns 2006), to our knowledge, this is the first to examine these factors systematically in a conceptual framework. Planning for comprehensive services is held back by our limited understanding of the characteristics associated with greater unmet need among families of children with ASD.…”
Section: Methodological Strengthsmentioning
confidence: 93%
“…Their inter-rater agreement, which allows one, scale-step difference, was 85% between parents and teachers and between parents and specialists (Bailey et al, 1993). The Swedish translation of the ABILITIES inter-rater agreement was 72% between parents and special educators (Granlund & Roll-Pettersson, 2001) and the stability of test-retest for special educator ratings was 90% .…”
Section: Methodsmentioning
confidence: 94%
“…In addition, some of these parents may have an ID themselves (David et al 2013). When combined, these difficulties increase the probability that families with a child with an MID must handle daily situations that differ from those of other families with regard to daily routines, social activities, and coping skills, as well as contact with support services (Granlund and Roll-Pettersson 2001;Webster et al 2008). Common needs of most families with children having disabilities include informational demands, knowledge, and skills regarding how to collaborate with professionals, maintaining parental influence over services, and understanding their children's rights (Bailey et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The questions were answered using a three-point scale with the options yes, unsure, or no. The questionnaire has been tested previously for reliability and validity in Sweden (Granlund and Roll-Pettersson 2001). Perceived needs are divided into indexes.…”
Section: Questionnairementioning
confidence: 99%